2013
DOI: 10.1111/fpa.12018
|View full text |Cite
|
Sign up to set email alerts
|

Eisenhower's Scientists: Policy Entrepreneurs and the Test-Ban Debate 1954-1958

Abstract: What accounts for the variation in the influence of scientists in the policy‐making process? Why is it that scientists sometimes appear to exercise significant autonomy in shaping policy agendas, while at other times very little? Scientists are most influential, this paper contends, when they can leverage their recognized expertise by strategically co‐opting institutionalized channels of advice. This is most likely to occur in issue areas of high complexity and ambiguity when key policy makers are dependent up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The documents consisted of minutes taken during network meetings, as well as the governmental document calling for the establishment of coordination networks nationwide. In line with case studies on policy entrepreneurship, we first identified the policy entrepreneurs ourselves (see for example, David, 2015;Mintrom, 2013;MacDonald, 2015;Meydani, 2009;. This is the case even in studies involving large numbers of policy entrepreneurs (see Brouwer & Huitema, 2015), though Mintrom's (2000) large N study relied on clerks identifying the policy entrepreneurs thus eliminating the attendant bias.…”
Section: Methodsmentioning
confidence: 99%
“…The documents consisted of minutes taken during network meetings, as well as the governmental document calling for the establishment of coordination networks nationwide. In line with case studies on policy entrepreneurship, we first identified the policy entrepreneurs ourselves (see for example, David, 2015;Mintrom, 2013;MacDonald, 2015;Meydani, 2009;. This is the case even in studies involving large numbers of policy entrepreneurs (see Brouwer & Huitema, 2015), though Mintrom's (2000) large N study relied on clerks identifying the policy entrepreneurs thus eliminating the attendant bias.…”
Section: Methodsmentioning
confidence: 99%
“…Policy entrepreneurs have proven to be significant in various policy areas such as public education (Mintrom, 2000;Mintrom, Salisbury and Luetjensm, 2014), child support (Crowley, 2003), energy policy (Cohen and Naor, 2013), environmental policy (Rabe, 2004), health care policy (Cohen, 2012;Oliver and Paul-Shaheen, 1997), disposal of radioactive waste (Ringius, 2001), anti-corruption policy (Navot and Cohen, 2015) and foreign affairs (Arieli and Cohen, 2013;Macdonald, 2013). They play a role in many countries (Ackrill, Kay and Zahariadis, 2013), including Australia and New Zealand (MacKenzie, 2004;Mintrom, 2006), the UK (Petchey, Williams and Carter, 2008), Sweden (Guldbrandsson and Fossum, 2009;Reinstaller, 2005), Israel and Jordan (Arieli and Cohen, 2013), Spain (Gallego and Barzelay, 2010), China (Zhu, 2008), India (Rutledge, 2012), Turkey (Ugur and Yankaya, 2008), Italy and Greece (Tsarouhas, 2012) and the US.…”
Section: Policy Entrepreneurship: Historical and Intellectual Developmentioning
confidence: 99%
“…In democratic systems like the United States, leaders may exhibit varying ideas about and degrees of support for multilateralism and principles regarding nonproliferation, as a function of political ideologies, socialization, and worldviews (Checkel ; Lantis ). Thus norms are not set in stone when they are institutionalized, rather they are shaped and reshaped by elite discourse regarding their meaning and relevance (Macdonald ; Panke and Petersohn ; Wiener ). Sikkink (, 2) argues that careful attention to “the role of human agency in the origins of new norms and practices” will empower models “better positioned to explain change.” Recognizing different perspectives toward norms, as well as the ways agents develop them and interact with others, may help explain the puzzle of inconsistencies in U.S. export policies, including patterns of liberal exporting and retrenchment and the question of why the United States would not quickly “reward” regional allies with NCAs.…”
Section: A Constructivist Model Of Nuclear Export Policiesmentioning
confidence: 99%